Gestão do conhecimento: mapeamento das práticas e ferramentas para o compartilhamento do conhecimento em uma instituição pública de ensino superior - Maronato, Elissandra Luiz dos Santos (2018)
Knowledge in the organization is acknowledged as a valuable asset. Access and effective use of knowledge assets is positively related to organizational performance. Knowledge sharing is a support mechanism for the necessary knowledge to be available. As individuals share knowledge in the organizational environment, more and more people can use this resource while creating new knowledge and, at the same time, discovering new methods to improve processes, products and services, that is, organizational performance as a whole. In this context, the objective of this research is mapping the Knowledge Management practices and tools for knowledge sharing in a public institution of higher education. The methodology, qualitative in nature, using a descriptive and exploratory approach, is based on a case study, with bibliographic research as a theoretical basis. Therefore, to identify the practices, the technological tools and the elements that enable the knowledge exchange, a selfadministered questionnaire with 36 statements was elaborated, which was answered for 14 public servants of the Planning and Administration Department of the Londrina campus of the Federal Technology University – Paraná. It was identified all the enablers elements investigated (trust, reciprocity, organizational culture, leadership, recognition, knowledge management systems and communication), specially trust and recognition. Regarding the practices, the results show the only two of the investigated practices are noted for the major part of the participants, continuous learning. These practices are corporate education and peer-assistance. Regarding the technological tools, it was verified that seven of the thirteen tools investigated are noted (e-mail, electronic management of documents, instant messages, intranet, corporative website, audio and videoconference systems, and workflow systems). The results analysis enables to have a general view about knowledge sharing real situation in the organizational context that is investigated. Hence, the Knowledge Management Practices Manual for knowledge sharing will contribute to the efficiency and the decision-making process, keys elements to the organization of work and processes in public institutions of higher education.